PENGARUH TINGKAT PENDIDIKAN DAN KEAHLIAN PROFESIONAL TEHADAP EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL DENGAN PENGALAMAN KERJA SEBAGAI MODERASI - Ni Luh Putu Sri Darmayanti (UNHI Press, 2021)
The effectiveness of the system and internal control is the level of achievement and program results with the targets set by the management and management designed to gain confidence and confidence about the achievement of organizational goals and objectives. To increase the effectiveness of systems and internal controls there are several things that must be considered. This research aims to find out the effect of the level of education and professional expertise on the effectiveness of the system and internal control with experience and work as moderation. This research was carried out at the Regional Owned Enterprises Badand Denpasard Kotad namely PDAM, PD Pasard and PD Parking. In this research, the method of purposived sampling was selected and the sample size was 32 respondents. Techniques and data analysis used in this research are descriptive statistics, validity mosque, reliability mosque, classical assumptions mosque, MRA, coefficient of determination, Ujid Fd and Ujid t. The results of the research showed that the level of education was positive with a positive coefficient of 0.374, the t-value was 2.312 and the significant value was 0.031 <0.05 and professional expertise was positive with a positive coefficient of 0.642, the t-value was as large as 2,789 and had a significant effect of <0.05d. positive and effectiveness of systems and internal control. The work experience variable with moderated 1 had a positive coefficient of 0.091, a t-value of 0.602 and a significant value of 0.511> 0.05 and moderated 2 had a negative coefficient of -0.122, a t-value of 0.602 and a significance of 0.511> 0.05 and moderated 2 had a negative coefficient of -0.122, the t-value of 0.18 and a significant of 0.282> 0.05. can not be able to modify the influence of the level of education and professional skills and effectiveness of the system and internal control.